Taekwondo training reduces blood catecholamine levels and arterial stiffness in postmenopausal women with stage-2 hypertension: randomized clinical trial - Sang Ho Lee; Steven D. Scott; Elizabeth J. Pekas; Seungyong Lee; Seok Hoon Lee; Song Young Park (Clinical and Experimental Hypertension, 2019)
Objective: Menopause is associated with a progressive impairment of vascular function and muscular strength in women. Accordingly, the purpose of this study was to determine if Taekwondo training could improve blood catecholamine levels, arterial stiffness, blood pressure (BP) and skeletal muscle strength in postmenopausal women with stage-2 hypertension. Methods: 20 postmenopausal women (70 ± 4 years old) with stage-2 hypertension were randomly assigned to a 1) Taekwondo training (TT; n = 10) or 2) Control (CON; n = 10) group. Taekwondo training was performed for 60 minutes/day, 3 days/week for 12-weeks. Results: There were significant (P < 0.05) group by time interactions for resting epinephrine (EP) and norepinephrine (NE) levels, with EP decreasing in the TT group and NE increasing in the CON group. Additionally, brachial-ankle pulse wave velocity, resting heart rate, and BP were significantly decreased, while hand grip and leg strength were significantly increased in the TT group compared to CON group. Conclusion: These results suggest that Taekwondo training can be a novel and beneficial mode of exercise for improving cardiovascular function and muscular strength in this population. Abbreviations: TT: Taekwondo training group; CON: control group; EP: epinephrine; NE: norepinephrine; ANS: autonomic nervous system; SNS: sympathetic nervous system; baPWV: brachial-ankle pulse wave velocity